2010
DOI: 10.1007/s00436-010-1880-4
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal activity of 94 extracts from ten plant species of northeastern of Brazil against Aedes aegypti L. (Diptera: Culicidae)

Abstract: In an effort to find effective and affordable ways to control of Aedes aegypti L. (Diptera: Culicidae), the larvicidal activities of 94 extracts from ten plant species belonging to eight families [Guettarda grazielae and Spermacoce verticillata (Rubiaceae), Coccoloba mollis and Triplaris americana (Polygonaceae), Eschweilera ovata (Lecytidaceae), Merremia aegyptia (Convolvulaceae), Ouratea nitida (Ochnnaceae), Protium heptaphyllum (Burseraceae), Rourea doniana (Connaraceae), and Tovomita brevistaminea (Guttife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 16 publications
1
48
0
Order By: Relevance
“…There are few published studies of this plant in the scientific literature. Hexane extracts of stem, bark and leaves of C. mollis have demonstrated larvicidal activity against Aedes aegypti, showing potential in the control of this vector of tropical diseases (Oliveira et al, 2010). In another study testing the ethanolic extracts of the leaves and roots of C. mollis, the results showed that both extracts induced the DNA damage at a concentration of 20 µg/mL, but neither showed genotoxicity at any of the concentrations tested, based on the micronucleus test (Tsuboy et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There are few published studies of this plant in the scientific literature. Hexane extracts of stem, bark and leaves of C. mollis have demonstrated larvicidal activity against Aedes aegypti, showing potential in the control of this vector of tropical diseases (Oliveira et al, 2010). In another study testing the ethanolic extracts of the leaves and roots of C. mollis, the results showed that both extracts induced the DNA damage at a concentration of 20 µg/mL, but neither showed genotoxicity at any of the concentrations tested, based on the micronucleus test (Tsuboy et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, when compared to synthetic insecticide Temephos (LD 50 8.7 μg/mL), only hexane fraction from stem (LD 50 72.08 g/mL; 95% CL 60.92-82.47) was effective. All others were inactive (LD 50 > 280 g/mL; results not shown in Table 1) (Oliveira et al, 2010). The isolation and purification of this extract and evaluation of these compounds will be needed to identify the active component.…”
Section: Resultsmentioning
confidence: 97%
“…Since there is no vaccine currently available for dengue and DHF prevention, the eradication of the mosquito adults and larvae, which is primarily relied on applications of synthetic insecticides or larvicides, is the most commonly adopted strategy for reducing morbidity (WHO, 2008). According to the literature, the organophosphate temephos is one of the most employed commercial insecticides for the control of this vector (Macoris et al, 2007;Garcez et al, 2009;Oliveira et al, 2010). However, these chemicals can affect non target population and may increase mosquito resistance to insecticides.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations